Effectiveness of wheel-typed grain design for hybrid rocket motor performance - Kafafy, Raed Ismail; Azami, Hanafi; Idres, Moumen (2013)
Although hybrid rockets are featured with distinct advantages over solid and liquid rockets, the issues specifically related to combustion instability and lowered regression rate are the most pronounced drawbacks which hinder it from being commercially viable. In the present work, we investigate the characteristics of hybrid rocket performance using generic algorithm code for preliminary design analysis purposes. An interior ballistic model is used for the analysis of the hybrid rocket performance. MATLAB® environment is used to develop the design and performance analysis codes, and visualize the temporal variation of performance characteristics. Hydroxyl Terminated Polybutadiene (HTPB) is used as a solid fuel and liquefied oxygen as an oxidizer for evaluation purposes. We have evaluated some other design features such as different expansion ratio for nozzle, different oxidizer initial flux and variation of initial mass. The valuation of variety port numbers are presented as well as comparison of multiple circular grain design. It was found that wheel-typed grain design improves 5% on the regression rate. The uses of many ports also improvise the regression rate but require a large diameter for structural integrity.